VD_FINDINFO HC / 2012 / 747 vom 1. November 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, DROIT DE GARDE, OBLIGATION D'ENTRETIEN, CONJOINT, MINIMUM VITAL | 163 al. 1 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 273 al. 1 CC, 273 al. 2 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)